Absolute risk-based treatment using adaptive blood pressure thresholds and targets is crucial to older multimorbid patients with high fall risk - Oh, VMS (Ovid Technologies (Wolters Kluwer Health), 2022)
10.1161/HYPERTENSIONAHA.118.11297